Synthesis, anti-oomycete activity, and SAR studies of paeonol derivatives. Issue 2 (1st February 2021) - Tian, Yue-E; Sun, Di; Han, Xiao-Xiao; Yang, Jin-Ming; Zhang, Song; Feng, Nan-Nan; Zhu, Li-Na; Xu, Zhong-Yuan; Che, Zhi-Ping; Liu, Sheng-Ming; Lin, Xiao-Min; Jiang, Jia; et al.
Abstract: Three series of sulfonate derivatives of paeonol were synthesized and screened in vitro for their anti-oomycete activity against P. capsici, respectively. Among all the compounds, 4m displayed the best promising and pronounced anti-oomycete activity against P. capsici than zoxamide, with the EC50 values of 24.51 and 26.87 mg/L, respectively. The results show that acetyl and 4-OCH3 are two necessary groups. The existence of these two sites is closely related to the anti-oomycete activity. Relatively speaking, hydroxyl group is well tolerated, and the results showed that after modification of hydroxyl group with sulfonyl, the anti-oomycete activity was significantly increased.